The Fuzzy TOPSIS Approach to Assessing Obesity Risk in a Comprehensive Range of Disease Factors - Thiravidarani J, Gunasekar T, Selvaraj A (Mathematical Statistician and Engineering Applications, 2022)
TOPSIS (“Technique for Order of Preference by Similarity to Ideal Solution”) is a ranking system which is used to rank the criteria in decision making problems. In many real-world situations, decision data of human judgments is often ambiguous and making traditional techniques of using crisp numbers becomes unsuitable. When the uncertainties occur at eight different points, triangular and trapezoidal numbers are not viable. As a result, the TOPSIS approach is extended to study the obesity risk factors using octagonal fuzzy numbers. Further, their arithmetic operations, as well as linguistic values are derived.